2018
DOI: 10.1371/journal.pone.0190714
|View full text |Cite
|
Sign up to set email alerts
|

Facial responsiveness of psychopaths to the emotional expressions of others

Abstract: Psychopathic individuals show selfish, manipulative, and antisocial behavior in addition to emotional detachment and reduced empathy. Their empathic deficits are thought to be associated with a reduced responsiveness to emotional stimuli. Immediate facial muscle responses to the emotional expressions of others reflect the expressive part of emotional responsiveness and are positively related to trait empathy. Empirical evidence for reduced facial muscle responses in adult psychopathic individuals to the emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 77 publications
(126 reference statements)
0
19
1
Order By: Relevance
“…However, the findings regarding facial mimicry in individuals with psychopathic traits are varied; for instance, Book et al (2015) showed that individuals with psychopathic traits had intact ability to accurately mimic the emotional expression of fear and remorse, but additional work assessing mimicry in a nonclinical population found that individuals with high psychopathic traits had difficulties reflecting negative emotions in others (e.g., anger, fear, disgust, or sadness) but not positive emotions (e.g., happiness and smiles) (Khvatskaya & Lenzenweger, 2016;Owens et al, 2017). In contrast, Künecke et al (2018) found no differences in facial reactivity between psychopathic offenders and a control group.…”
Section: Antisocial Behavior Psychopathy and Facial Expressivitycontrasting
confidence: 61%
“…However, the findings regarding facial mimicry in individuals with psychopathic traits are varied; for instance, Book et al (2015) showed that individuals with psychopathic traits had intact ability to accurately mimic the emotional expression of fear and remorse, but additional work assessing mimicry in a nonclinical population found that individuals with high psychopathic traits had difficulties reflecting negative emotions in others (e.g., anger, fear, disgust, or sadness) but not positive emotions (e.g., happiness and smiles) (Khvatskaya & Lenzenweger, 2016;Owens et al, 2017). In contrast, Künecke et al (2018) found no differences in facial reactivity between psychopathic offenders and a control group.…”
Section: Antisocial Behavior Psychopathy and Facial Expressivitycontrasting
confidence: 61%
“…This kind of expression is the result of an activated motor system (Goldman & Sripada, 2005) associated with empathy (e.g., Harrison et al, 2010), and preventing spontaneous expression of a perceived emotion impedes the ability to perceive emotions (e.g., Lobmaier & Fischer, 2015). While psychopathy is partially defined as lacking empathy (Hare, 2003), a recent study found psychopathy is actually unrelated to these spontaneous expression of a perceived emotion (Künecke et al, 2018)…”
Section: Psychopathy and Emotion Expressionmentioning
confidence: 99%
“…While continued research on mechanisms of change and long-term outcomes is necessary, early interventions may disrupt the development of meanness characteristics and promote the capacity for loving relationships with others. Considered in the context of findings by Künecke, Mokros, Olderbak, and Wilhelm (2018), suggesting that psychopathic traits may be associated with an unwillingness to empathize with others as opposed to an inability to empathize, early interventions may foster skills and willingness related to developing emotional connectedness with others. Given the current study's findings on the links between the love constructs and physical and psychological aggression in relationships, improving one's ability to develop closeness and commitment to partners may thereby be one path to decreasing intimate partner violence.…”
Section: Implications and Future Directionsmentioning
confidence: 99%